ACCOUNTING INFORMATION IN THE SYSTEM OF FORMATION OF ANTI-CRISIS MANAGEMENT OF PERSONNEL OF AGRICULTURAL ENTERPRISES - Maletska , O.I.; Prokopyshyn , O. S.; Myronchuk , Z.P. (The actual problems of regional economy development, 2020)
The article is aimed at determining the methodology formation of the system crisis management personnel of agricultural enterprises. The method of personnel analysis, their testing, professional qualification characteristics, compliance professional skills individual employees with their positions in order to increase the efficiency the personnel of the enterprise are studied. In addition, it was argued that for agriculture, which occupies the last place in the implementation of progressive forms labor organization and production process management, adaptation of modern management experience, and especially for people management, is extremely necessary and relevant today. One such new approach is the transformation of HR staff into HR managers. The main regularities are identified, positive, which contribute to the achievement of the goals of the state employment policy, and negative, which hinder their achievement. The authors noted that the trends of the process of reproduction of the system of jobs remain uncertain patterns and trends of reproduction of the system of jobs of domestic enterprises and the economy in general and do not realize reserves to increase employment efficiency by increasing the validity of state policy to create jobs and dissemination of models of economic behavior focused on the expanded intensive reproduction of the workplace system. It is established that anti-crisis personnel management is an important component of enterprise management and has a significant impact on the efficiency of its economic activity.